Anticorrosion Behaviour of Rhizophora mangle L. Bark-Extract on Concrete Steel-Rebar in Saline/Marine Simulating-Environment - Joshua Olusegun Okeniyi; Jacob Olumuyiwa Ikotun; Esther Titilayo Akinlabi; Elizabeth Toyin Okeniyi (The Scientific World Journal)
This paper investigates anticorrosion behaviour of the bark-extract from Rhizophora mangle L. on steel-rebar in concrete slabs in 3.5% NaCl medium of immersion (for simulating saline/marine environment). Corrosion-rate, corrosion-current, and corrosion-potential were measured from the NaCl-immersed steel-reinforced concrete cast with admixture of different plant-extract concentrations and from positive control concrete immersed in distilled water. Analyses indicate excellent mathematical-correlation between the corrosion-rate, concentration of the bark-extract admixture, and electrochemical noise-resistance (ratio of the corrosion-potential standard deviation to that of corrosion-current). The 0.4667% Rhizophora mangle L. bark-extract admixture exhibited optimal corrosion-inhibition performance, η = 99.08±0.11% (experimental) or η = 97.89±0.24% (correlation), which outperformed the positive control specimens, experimentally. Both experimental and correlated results followed Langmuir adsorption isotherm which suggests prevalent physisorption mechanism by the plant-extract on the reinforcing-steel corrosion-protection. These findings support Rhizophora mangle L. bark-extract suitability for corrosion-protection of steel-rebar in concrete structure designed for immersion in the saline/marine environmental medium.